Research on high-output-voltage power supply with wide input voltage range for electric propulsion system - Shi Kaimin; Zhang Donglai; Wang Zicai; Zhang Hua; Lv Wenqi (Dianzi Jishu Yingyong, 2021)
Power Processing Unit(PPU) is the central part of the xenon ion electric propulsion system, and its size, weight, and key technical difficulties usually exceed the thruster itself. The high-power and high-output-voltage power supplies, such as beam supply and anode supply, are the main parts of the electric propulsion power system. In this paper, a two power stage beam supply topology is proposed to meet the requirement of multi-mode electric propulsion system. The front stage is an interleaved boost converter, which is adopted to adjust the total output voltage. The second stage is based on a full-bridge resonant converter able to provide very high output voltage, which operates the fixed optimum switching frequency. The power converter control strategy and design principles of magnetic components are studied and finally the corresponding experimental results are given to validate feasibility of the proposed converter in this paper.